PENGARUH PEMBERIAN JUS KACANG HIJAU (PHASEOLUS RADIATUS) TERHADAP PENINGKATAN KADAR PROFIL DARAH PADA IBU HAMIL DENGAN ANEMIA YANG MENDAPATKAN SUPLEMENTASI TABLET FE (STUDI KASUS DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU SEMARANG) - Stefani Anastasia Sitepu (JURNAL KEBIDANAN KESTRA (JKK), 2018)
Anemia is a reduction in the number of red blood cells or hemoglobin content in the blood. The biggest group who can experience anemia are pregnant women. The causes of anemia in pregnant women include the production of the hemoglobin chain due to a certain disease or a disruption of hemoglobin production due to lack of iron, folic acid or vitamin B12. Research purposes : Knowing the effect of giving green bean juice (Phaseolus Radiatus) to changes in blood profile levels in pregnant women with anemia who received Fe tablet supplementation. This research design was quasi-experimental with nonrandomized pretest and posttest with control group design. This study was conducted for 7 weeks. The number of samples in this study were 40 respondents (20 mothers of the intervention group who received green bean juice and Fe tablet supplementation and 20 respondents who only received Fe tablet supplementation). Samples were obtained using purposive sampling. Evaluation of blood profile levels was carried out after giving green bean juice on day 15. The results showed an increase in hemoglobin levels, hematocrit, and erythrocytes (p = 0,000), meaning that the administration of mung bean juice to pregnant women with anemia affects the increase in hemoglobin levels, hematocrit, and erythrocytes. For health services, it is expected that mung bean juice can be used as an alternative to overcome anemia in pregnant women.